STRATEGY TO IMPROVE TEACHER WORK ETHIC AT ISLAMIC JUNIOR HIGH SCHOOL AL-ULUM TERPADU MEDAN - Tantri, Arya; Wijaya, Candra (Pena Cendekia Insani, 2025)
Teachers' work ethic plays a vital role in enhancing standards of education, especially in creating a meaningful learning process and contributing to the formation of students' character. This research seeks to explore the leadership approach in encouraging the improvement of teachers' work ethic at SMP Islam Al-Ulum Terpadu Medan. The research employed a qualitative descriptive method via interviews, observations, and documentation. The findings show that the strategies implemented include routine training, providing appreciation, fostering discipline, a participatory approach in decision-making, and creating an Islamic and comfortable work environment. The success of this strategy is supported by the availability of adequate facilities, synergy between teachers, and full support from the principal. The obstacles that arise include work saturation, low motivation of some teachers, and limited facilities. The strategy has been proven to be able to increase teacher enthusiasm, discipline, and professionalism. The study concluded that participatory leadership and a supportive work environment are important factors in the success of improving work ethic. The researcher recommends periodic evaluation, strengthening technology-based training, and expanding similar research in other schools to broaden the understanding and application of strategies to improve work ethic as a whole.